Effectiveness of Multiple Representations for Learning Energy Concepts: Case of Turket - KURNAZ, Mehmet Altan; SAĞLAM ARSLAN, Ayşegül (Procedia - Social and Behavioral Sciences 116 ( 2014 ) 627 – 632 5th World Conference on Educational Sciences - WCES 2013, 2013)
The aim of this paper was to investigate the effects of multiple representations for students to learn the energy concepts. To this end, a learning environment for the energy concept of introductory physics course was designed. The learning environment was constructed by means of multiple representations embedded within MOMBI model. The process was carried out with the participation of 68 freshmen and this paper highlights some half-constructive-interview results conducted with 11 of the participants. The interviewers were volunteers, and they were asked four questions. Findings indicated that although majority of the students come to university with non-scientific ideas for the energy concept, the learning environment based on multiple representations have positive effects to remedy non-scientific student ideas. Analyses of student answers especially put forth that the learning environment encourages students to explain characteristics of the energy concept. Baked by the results, it was suggested to use multiple representations such as tables, data-meaning tables, conceptual change texts, concept maps and analogies to improve students’ conceptual understanding about the energy concept.
Keywords: Multiple representations; energy concept; freshmen